2013
DOI: 10.15376/biores.8.2.2510-2520
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Properties of Alkaline Lignin / Poly (Vinyl Alcohol) Blend Membranes

Abstract: Membranes were prepared from alkaline lignin and poly(vinyl alcohol) (PVA) by a film casting method, and their properties were evaluated. These blend membranes can aptly be termed as green by nature as they are totally non-toxic and eco-friendly. The optimal mass ratio was determined based on the mechanical properties of membranes. The microstructure, mechanical properties, oxygen and carbon dioxide transmission, light transmittance, and thermal stability of the membranes were investigated. The blend membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…This formation of a new hydrogen bond between the lignin and the polymer matrix has been confirmed by several studies. 40 43 The small bands at 2939.92 cm –1 (neat PVA), 2939.60 cm –1 (OL/PVA), and 2939.01 cm –1 (OLPs/PVA) are assigned to the characteristic bands of CH 2 stretching vibration, while 2850.92 cm –1 (neat PVA), 2852.03 cm –1 (OL/PVA), and 2851.42 cm –1 (OLPs/PVA) are related to the stretching vibrations of the C–H. The bands observed at 1086.90 cm –1 (neat PVA), 1087.64 cm –1 (OL/PVA), and 1087.57 cm –1 (OLPs/PVA) were recognized as C–O stretching vibration in which similar results were also reported ( Figure 12 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…This formation of a new hydrogen bond between the lignin and the polymer matrix has been confirmed by several studies. 40 43 The small bands at 2939.92 cm –1 (neat PVA), 2939.60 cm –1 (OL/PVA), and 2939.01 cm –1 (OLPs/PVA) are assigned to the characteristic bands of CH 2 stretching vibration, while 2850.92 cm –1 (neat PVA), 2852.03 cm –1 (OL/PVA), and 2851.42 cm –1 (OLPs/PVA) are related to the stretching vibrations of the C–H. The bands observed at 1086.90 cm –1 (neat PVA), 1087.64 cm –1 (OL/PVA), and 1087.57 cm –1 (OLPs/PVA) were recognized as C–O stretching vibration in which similar results were also reported ( Figure 12 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Poly(vinyl alcohol) contains numerous hydroxyl groups capable of donating hydrogens to the oxygen-containing functional groups of lignin, thus it is expected to be miscible, but at least compatible with lignin. Quite a few studies have been carried out on this combination of materials and most of the authors concluded that they form heterogeneous blends [43,[46][47][48][49], which contradicts the expectations and is quite surprising.…”
Section: Introductionmentioning
confidence: 92%
“…As described in the introductory part, the opinions on the structure of polymer/lignin blends differ considerably among groups and authors. Miscibility was claimed even for polyolefin/lignin blends [50], while heterogeneous structure was found for example for the PVOH/lignin pair [46][47][48][49]…”
Section: Structurementioning
confidence: 99%
“…The importance of hydrogen bonds was pointed out in several publications by a number of authors. They were thought to be significant in poly(vinyl chloride) [31,33], poly(vinyl alcohol) [34,35], poly(lactic acid) [37][38][39], and polyhydroxybutyrate [42,43]. In spite of the importance of hydrogens bonds, Doherty et al [54] claimed that they alone are not sufficient to compete successfully with the strong interactions among lignin molecules and to result in complete miscibility.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of papers have been published on the blends of lignin with a wide range of polymers including proteins [10][11][12], starch [13][14][15], polyolefins [16][17][18][19][20][21][22][23][24][25][26], vinyl polymers 4 [18,19,21,[27][28][29][30][31][32][33][34][35] and polyesters [19,21,22,[36][37][38][39][40][41][42][43]. The chemical modification of lignin [10,14,16,[20][21][22]27,29,36,40,…”
Section: Introductionmentioning
confidence: 99%